(2x+7i)(2x-7i)=

Simple and best practice solution for (2x+7i)(2x-7i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+7i)(2x-7i)= equation:


Simplifying
(2x + 7i)(2x + -7i) = 0

Reorder the terms:
(7i + 2x)(2x + -7i) = 0

Reorder the terms:
(7i + 2x)(-7i + 2x) = 0

Multiply (7i + 2x) * (-7i + 2x)
(7i * (-7i + 2x) + 2x * (-7i + 2x)) = 0
((-7i * 7i + 2x * 7i) + 2x * (-7i + 2x)) = 0

Reorder the terms:
((14ix + -49i2) + 2x * (-7i + 2x)) = 0
((14ix + -49i2) + 2x * (-7i + 2x)) = 0
(14ix + -49i2 + (-7i * 2x + 2x * 2x)) = 0
(14ix + -49i2 + (-14ix + 4x2)) = 0

Reorder the terms:
(14ix + -14ix + -49i2 + 4x2) = 0

Combine like terms: 14ix + -14ix = 0
(0 + -49i2 + 4x2) = 0
(-49i2 + 4x2) = 0

Solving
-49i2 + 4x2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-4x2' to each side of the equation.
-49i2 + 4x2 + -4x2 = 0 + -4x2

Combine like terms: 4x2 + -4x2 = 0
-49i2 + 0 = 0 + -4x2
-49i2 = 0 + -4x2
Remove the zero:
-49i2 = -4x2

Divide each side by '-49'.
i2 = 0.08163265306x2

Simplifying
i2 = 0.08163265306x2

Take the square root of each side:
i = {-0.285714286x, 0.285714286x}

See similar equations:

| f(3)=2f(1) | | A+17=4(A-2)-5+3A | | x^4-7x^3-10x^2+7x+1=0 | | 4x+8=202 | | 8w+5=4(2+1)w | | 0.09xX=77.01 | | C/4=11 | | 13y+7y+(6y+6)=34 | | -6x+-12=42 | | x^2-55x+204=0 | | 0.09xX=62.95 | | 2y+25-19=0 | | 5x+2=x+8T | | 2-3x=-5x+16 | | 6x+13=x+8 | | 5x-4=2(4x+4)-3 | | n/5.5=2 | | 7/8x5/9 | | 2x+5=3(2x-4) | | 7/8x2/9 | | 7x-35=3x+5 | | 7x+5x-3=21 | | y=0.60x+46 | | 2x+122=12x-8 | | 24=86 | | 2(3X-5)=27 | | lnx=2-2x | | 30=(2*11)+2w | | 5x+6=2x+60 | | 9=.5q | | a/3=-14 | | 12x^11=15 |

Equations solver categories